2022
DOI: 10.3389/fcell.2021.792401
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of LncRNA Regulation for NLRP3 Inflammasome in Diabetes Complications

Abstract: Diabetes is a widespread metabolic disease with various complications, including diabetic nephropathy, retinopathy, cardiomyopathy, and other cardiovascular or cerebrovascular diseases. As the prevalence of diabetes increases in all age groups worldwide, diabetes and its complications cause an emerging public health burden. NLRP3 inflammasome is a complex of several proteins that play a critical role in inflammatory response and various diseases, including diabetes and its complications. Accumulating evidences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 108 publications
0
15
0
Order By: Relevance
“…In an addition, the effect of L13Rik on DN progression will be investigated in diabetic rats. Mounting studies have demonstrated that lncRNA functions as important mediator in DN or other diabetic complications (Lu et al, 2021). For instance, lncRNA MSC-AS1 is up-regulated in peripheral blood from DN patients, and MSC-AS1 silencing alleviates HG-triggered MC proliferation, fibrosis, and inflammation through sponging miR-325 and de-repressing cyclin G1 (Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In an addition, the effect of L13Rik on DN progression will be investigated in diabetic rats. Mounting studies have demonstrated that lncRNA functions as important mediator in DN or other diabetic complications (Lu et al, 2021). For instance, lncRNA MSC-AS1 is up-regulated in peripheral blood from DN patients, and MSC-AS1 silencing alleviates HG-triggered MC proliferation, fibrosis, and inflammation through sponging miR-325 and de-repressing cyclin G1 (Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of pro-inflammatory factors may further induce DM complications (31). In recent years, multiple studies have suggested that NLRP3 inflammasome is related to DM and its complications (32). For example, Tseng et al demonstrated that hyperglycemia high glucose induces activation of NLRP3-ASC inflammasome, leading to casparase-1 activation and secretion of IL-1b and IL-18 in human monocyte cell lines (33).…”
Section: Dm and Nlrp3mentioning
confidence: 99%
“…The overexpression of pro-inflammatory factors may further induce DM complications ( 31 ). In recent years, multiple studies have suggested that NLRP3 inflammasome is related to DM and its complications ( 32 ). For example, Tseng et al.…”
Section: Nlrp3mentioning
confidence: 99%
“…Specifically, inflammatory factors decrease the activities of insulin receptor in hepatocytes, muscle cells, and adipocytes, accompanied by insulin receptor substance-induced intracellular signaling transduction inhibition, glucose transporter generation and translocation suppression, and glucose uptake and metabolism disruption ( Passarelli and Machado, 2021 ; Xiao et al, 2022 ). A hyperglycemic environment facilitates the occurrence of inflammation and oxidative stress, which exacerbate vascular and myocardial complications and enhance the risks of diabetic disability and mortality ( Lu et al, 2021 ; Semwal et al, 2021 ; Yu et al, 2022 ). There is evidence showing that KD administration effectively decreased blood glucose content, elevated circulating insulin level, prevented weight gain, and improved glucose tolerance in streptozotocin-induced hyperglycemic rats, without causing toxicity.…”
Section: Potentials Of Kd Against Disease Developmentmentioning
confidence: 99%